HARMONIC OSCILLATOR WITH RANDOM DRIVEN FACTORS - KUSMONO (NIM : 10109015); pembimbing : Jalina Widjaja, Ph.D ; Yudi Soeharyadi, Ph.D, WILLIAM
Oscillator is a system producing amplitude which varies periodically over time. In reality, there are many external forces which drivethe harmonic oscillator. Since the driven factors are too many and too complicated to be tracked down and to be included in the system, the whole external forces is assumed to be random. In this report of Final Project, we will discuss a harmonic oscillator with random driven factors. The study of calculus stochastic like Brownian Motion, stochastic integrals and Itos Formula, and stochastic differential equations are necessary. This is a literature study for explaining the phenomena of harmonic oscillators with random driven factor.